Remote work adoption’s influence on engagement, job satisfaction, discretionary effort and turnover intention : insights from remote workers in a post-Covid-19 pandemic business environment - Balkissoon, Rishal (University of Pretoria, 2023)
Mini Dissertation (MBA)--University of Pretoria, 2022.